2019
DOI: 10.3389/fimmu.2019.01712
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of the C1q-Binding Ability and the IgG1-4 Subclass Profile of Preformed Anti-HLA Antibodies by Solid-Phase Assays

Abstract: Humoral alloimmunity, particularly that triggered by preformed antibodies against human leukocyte antigens (HLA), is associated with an increased prevalence of rejection and reduced transplant survival. The high sensitivity of solid phase assays, based on microbeads coated with single antigens (SAB), consolidated them as the gold-standard method to characterize anti-HLA antibodies, ensuring a successful allograft allocation. Mean fluorescence intensity (MFI) provided by SAB is regularly used to stratify the im… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 46 publications
0
8
0
Order By: Relevance
“…Our findings resembles those recently published by Navas et al demonstrating a close relationship between the circulating antibody strength, the presence of a mixture of IgG subclasses, beyond the quasy omnipresent IgG1, and the complement-binding ability measured by C1q. 32 Important to mention are the results obtained in this study in relation to the low frequency detected for both IgG subclass identification and C3d positivity which corresponded to 20.7% and 12.2%, respectively, of the total 1,771 HLA-Abs detected by the three methods used. Whether methodological factors could took place, at least in part in these results, cannot be ruled out despite the methods followed were exactly as the manufacturer indicate.…”
Section: Discussionmentioning
confidence: 58%
“…Our findings resembles those recently published by Navas et al demonstrating a close relationship between the circulating antibody strength, the presence of a mixture of IgG subclasses, beyond the quasy omnipresent IgG1, and the complement-binding ability measured by C1q. 32 Important to mention are the results obtained in this study in relation to the low frequency detected for both IgG subclass identification and C3d positivity which corresponded to 20.7% and 12.2%, respectively, of the total 1,771 HLA-Abs detected by the three methods used. Whether methodological factors could took place, at least in part in these results, cannot be ruled out despite the methods followed were exactly as the manufacturer indicate.…”
Section: Discussionmentioning
confidence: 58%
“…Optimal C1q engagement by the complement‐binding region of antibodies is mediated when anti‐HLA antibodies are bound to cell surface HLA molecules (particularly if HLA molecules are highly expressed) and arranged in a hexagonal pattern. Once bound to cell surface molecules on the endothelium, antibody subclasses IgG1 and IgG3 in particular, bind the complement component C1q, and initiate the classical complement cascade 82,83 . This results in the recruitment of leukocytes which further induce inflammation and allograft damage as well as direct lysis of the targeted cell through complement‐dependent cytotoxicity.…”
Section: Antibody‐mediated Rejectionmentioning
confidence: 99%
“…Additionally, there is a maximum detection limit ~20,000 MFI using the currently ubiquitous Luminex ® 100/200™, although the newer Luminex ® FLEXMAP 3D platform has been reported to have a greater detection range (up to 400,000 MFI), which may reduce saturation errors in the future (Gebel & Bray, 2019). The relative impact of saturation can only be proven by retesting following dilution of sera (McCaughan et al, 2019;Navas et al, 2019;Tambur & Wiebe, 2018). Similarly, the effects of prozone can be reduced by dilution or pre-treatment of sera using heat inactivation, ethylenediaminetetraacetic acid (EDTA) or dithiothreitol (DTT) to remove blocking factors (i.e., complement and IgM antibody respectively) (Anani et al, 2016;Battle et al, 2017;Courant et al, 2018;Gebel & Bray, 2019;Guidicelli et al, 2013;Middleton et al, 2014).…”
Section: Interference Factorsmentioning
confidence: 99%
“…The association between a high MFI value and complementfixing has been reported as a confounding factor for both the C1q and C3d assays (Cioni et al, 2017;Claisse et al, 2017;Courant et al, 2018;Gautier Vargas et al, 2019;Kamburova et al, 2018;Karahan et al, 2017;Ko et al, 2018;Moreno Gonzales et al, 2017;Schaub et al, 2014;Tait et al, 2013;Yell et al, 2015), although antibodies with high MFI value are not always reported to be complement fixing (Chen et al, 2011;Navas et al, 2019;Zeevi et al, 2012). As the density and avidity of bound antibody affects the efficiency of C1qbinding, it would suggest that lower titre antibodies (reported as 1:34 to 1:64 titre) (Tambur & Wiebe, 2018) may give a false negative result for assessment of complement-fixing ability (Filippone & Farber, 2016;Schaub et al, 2014;Tambur et al, 2015;Thurman et al, 2019).…”
Section: Clinical Relevance Of Luminex Sab ® Modification Assaysmentioning
confidence: 99%